Wykorzystanie naturalnych metod w ochronie winorośli = Natural methods of the vineyard protection - Czulak, Marzena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article undertakes the questions of the biological protection of the cultivable plants as the alternative to chemical methods. The real problem is connected with toxins in the environment which have the negative influence on functioning of the ecosystem.
Keywords: środowisko naturalne; ekosystem; toksyny; natural environment; ecosystem; toxins